Analysis of the usage of the Instagram account @arabiyahtalks as a tool for teaching Arabic to non-native speakers - Azlina, Vizi; Zainuddin , Darwin (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This research aims to analyze the quality of the Instagram account @arabiyahtalks as a learning media for Arabic language learners who are non-Arabic speakers, covering vocabulary materials in terms of content suitability, design suitability, presentation suitability, and language suitability. The research adopts a descriptive qualitative approach with a literature study design. Primary data sources are derived from the Instagram account @arabiyahtalks, while secondary data sources are from books, journals, and related literature. Data collection methods include documentation and literature study, and data analysis techniques employ content analysis. Based on the researcher’s analysis, the research findings indicate that the vocabulary presented in this account is done through two methods: first, using pamphlets/images, which received excellent ratings in all aspects, and secondly, through conversation videos, which received excellent ratings in language suitability and material suitability aspects, and good ratings in presentation suitability and design suitability aspects.